2016
DOI: 10.1186/s40478-016-0358-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of FUS-associated ALS and FTD: insights from rodent models

Abstract: Disruptions to genes linked to RNA processing and homeostasis are implicated in the pathogenesis of two pathologically related but clinically heterogeneous neurodegenerative diseases, amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Mutations in the Fused-in-Sarcoma (FUS) gene encoding a 526 amino-acid RNA-binding protein are found in a small subset of ALS cases, but FUS mutations do not appear to be a direct cause of FTD. Structural and functional similarities between FUS and another ALS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 95 publications
(146 reference statements)
1
86
0
1
Order By: Relevance
“…However, mice of L-FUS transgenic line with further reduced expression level of the same truncated variant of FUS in the spinal cord do not develop motor neuron pathology and have normal lifespan. 9,10 This is consistent with results of studies of other FUS transgenic mice that showed a direct correlation between the level of transgene expression and the severity of pathological changes 27. It is feasible that the low level of mislocalised pathogenic form of FUSF I G U R E 3 Water induced grooming test.…”
supporting
confidence: 80%
“…However, mice of L-FUS transgenic line with further reduced expression level of the same truncated variant of FUS in the spinal cord do not develop motor neuron pathology and have normal lifespan. 9,10 This is consistent with results of studies of other FUS transgenic mice that showed a direct correlation between the level of transgene expression and the severity of pathological changes 27. It is feasible that the low level of mislocalised pathogenic form of FUSF I G U R E 3 Water induced grooming test.…”
supporting
confidence: 80%
“…Of the ∟3% of ALS cases that do not have TDP-43 aggregation, FUS is analogously aggregated in ∟50% of these (Mackenzie et al 2007). However, unlike with TDP-43, FUS pathology never presents without FUS mutations, >50 of which have been described (Nolan et al 2016). Whereas disease-causing TDP-43 mutations are clustered in the C-terminal G-rich and Q/N regions, FUS mutations occur throughout the protein, although the most common and well-described are in the C-terminal NLS (Shang and Huang 2016;Svetoni et al 2016).…”
Section: Fusmentioning
confidence: 99%
“…ALS-linked mutations in FUS lead to the mislocalization of the protein to the cytoplasm from the nucleus (Munoz et al, 2009;Neumann et al, 2009;Dormann et al, 2010). Rodents and flies expressing wild type or mutant FUS developed defective phenotypes, such as synapse loss in the neuromuscular junction, aggregate formation in the cytoplasm, imbalance of mitochondrial dynamics, and mitochondrial dysfunction (Lanson Jr. et al, 2011;Altanbyek et al, 2016;Nolan et al, 2016). However, the molecular mechanisms underlying FUS-induced neuronal toxicity are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%